Reflection of Political and Social Development in the Religious Street Names of the City of Trnava and their Potential in Tourism - Judák, Viliam; Petrikovičová, Lucia; Grežo, Henrich; Akimjak, Amantius (Journal of Education Culture and Society, 2023)
Aim. From the point of view of the period of creation and historical development, we consider the streets of the historical core of Trnava to be the most dynamic, and why we focused on street name changes in the period from 1900 to the present in the area of the historical core of the city. Methods. As part of the methodology the classification by urbanonym, with the help of which we included the names of streets and squares into individual categories. A classification was used that divides urbanonyms into socially motivated and socially non-motivated, which are further divided into several subcategories. Urbanonyms are further divided into domestic and foreign. This classification is the most up-to-date of those mentioned and includes a category of religious names. Results. The category of socially significant street names, are divided at a lower level into the categories of politics, art and culture, church, science, crafts and trade, historical names and institutions. The most numerous is the group of names in the art and culture category, which includes 70 domestic and 10 foreign names, which together represent 25.89% of the total number of streets in the city. There are 15 streets in the categories of politics, church and science (4.85% of all 309 streets). Conclusion. Currently, Trnava can be characterised as a modern, dynamic city with a great influence on its surroundings. The restrictive measures taken in connection with the coronavirus pandemic in 2020 greatly affected the tourism sector and meant permanent closure for many businesses.